POLARIZATION AND FREQUENCY SELECTIVE CHARACTERISTICS OF A CHIRAL METASURFACE COMPOSED OF PERIODICALLY ARRANGED SQUARE DIELECTRIC HELICES - Yachin, V.; Zinenko, T.; Kochetova, L.; Mladyonov, P.; Mizrakhy, S. (Radio physics and radio astronomy (Print), 2023)
Subject and Purpose. The present study is concerned with the linearly polarized electromagnetic wave transmission through a chiral metasurface composed of periodically assembled square dielectric helices. We expect that the metasurface of the kind has a wider range of functional capabilities to transform a polarized wave into a cross-polarized one when compared to a similar metasurface composed of metal helices. Methods and Methodology. To find the scattering coefficients of the considered structure, the well-established method of integral functionals is followed. A set of volume integral equations in the vectorial form is solved for the equivalent electric and magnetic polarization currents of the analyzed periodic layer. A distinctive feature of the method is that the internal electromagnetic fields of the structure are initially found, whence the fields scattered by this structure are sought. The equations are discretized in terms of integral functionals related to the polarization currents and through the use of the double Floquet–Fourier series expansion technique. Results. It has been found that the metasurface transmission coefficients depend critically on the number of bars making the square helical particle. In the case of an even bar number, the chiral metasurface exhibits the same transmission coefficients for co- polarized field components in the event that linearly x- and y-polarized waves are incident. For cross-polarized field components, the transmission coefficients differ and can reach peak values at different frequencies. Finally, transmission coefficients of these polarizers have been investigated versus dimensions of helice-making bars. Conclusion. A wide variety of transmission properties observed in the metasurfaces make them particularly attractive for use in polarization converting and separating devices. The metasurface can feature dichroic asymmetric transmission and be used as a dichroic filter with polarization transformation. It can be put to use in differential phase sections and, also, as an effective dichroic cross-polarization converter (twist polarizer)